2022
DOI: 10.1016/j.celrep.2022.110339
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of plant microRNA-encoded peptides (miPEPs) reveals molecular mechanisms from the translation to activity and specificity

Abstract: MicroRNAs (miRNAs) are transcribed as long primary transcripts (pri-miRNAs) by RNA polymerase II. Plant pri-miRNAs encode regulatory peptides called miPEPs, which specifically enhance the transcription of the pri-miRNA from which they originate. However, paradoxically, whereas miPEPs have been identified in different plant species, they are poorly conserved, raising the question of the mechanisms underlying their specificity. To address this point, we identify and re-annotate multiple Arabidopsis thaliana pri-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 29 publications
3
54
0
Order By: Relevance
“…For a long time, miRNAs are considered the class of non-coding small RNAs. However, recent studies have shown that primary miRNAs (pri-miRNAs) can encode for regulatory peptides, called miRNA-encoded peptides (miPEPs), which specifically enhance the levels of mature miRNAs by increasing the transcription of corresponding pri-miRNA (Lauressergues et al, 2022). So far, miPEPs have been reported in plant species and even in animals (Dozier and Plaza, 2022).…”
Section: Roles Of Mirna Encoded Peptide In Plantsmentioning
confidence: 99%
“…For a long time, miRNAs are considered the class of non-coding small RNAs. However, recent studies have shown that primary miRNAs (pri-miRNAs) can encode for regulatory peptides, called miRNA-encoded peptides (miPEPs), which specifically enhance the levels of mature miRNAs by increasing the transcription of corresponding pri-miRNA (Lauressergues et al, 2022). So far, miPEPs have been reported in plant species and even in animals (Dozier and Plaza, 2022).…”
Section: Roles Of Mirna Encoded Peptide In Plantsmentioning
confidence: 99%
“…Several studies have shown that miRNA has an important regulatory role in biotic and abiotic stresses, such as nutrient deficiency conditions, which inhibit plant growth and development (Pagano et al, 2021; Basso et al, 2019; Fujii et al, 2005; Lin et al, 2013; Misra et al, 2010; Sharma et al, 2014). Research on miRNA-encoded peptides (miPEPs) began recently since a study revealed that a few pri-miRNAs have one or more open reading frames (ORFs), which regulate the associated miRNAs by enhancing their transcription (Lauressergues et al, 2015; Couzigou et al, 2015; Sharma et al, 2020; Lauressergues et al, 2022; Badola et al, 2022). Although the role of these miPEPs has been explored in various plants (Chen et al, 2020; Couzigou et al, 2016; Badola et al, 2022; Lauressergues et al, 2022) however, their mode of action under different stresses remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Research on miRNA-encoded peptides (miPEPs) began recently since a study revealed that a few pri-miRNAs have one or more open reading frames (ORFs), which regulate the associated miRNAs by enhancing their transcription (Lauressergues et al, 2015; Couzigou et al, 2015; Sharma et al, 2020; Lauressergues et al, 2022; Badola et al, 2022). Although the role of these miPEPs has been explored in various plants (Chen et al, 2020; Couzigou et al, 2016; Badola et al, 2022; Lauressergues et al, 2022) however, their mode of action under different stresses remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations